A novel SARS-CoV-2 related coronavirus with complex recombination isolated from bats in Yunnan province, China. Issue 1 (1st January 2021) - Li, Li-li; Wang, Jing-lin; Ma, Xiao-hua; Sun, Xiao-man; Li, Jin-song; Yang, Xiao-fei; Shi, Wei-feng; Duan, Zhao-jun
ABSTRACT: At the end of 2019, A new type of beta-CoV, SARS-CoV-2 emerged and triggered the COVID-19 pandemic, which spread overwhelmingly around the world in less than a year. However, the origin and direct ancestral viruses of SARS-CoV-2 remain unknown. RaTG13, a novel coronavirus found in bats in China's Yunnan Province, is the closest relative virus of the SARS-CoV-2 identified so far. In this study, a new SARS-CoV-2 related virus, provisionally named PrC31, was discovered in Yunnan province by retrospectively analyse bat next generation sequencing (NGS) data of intestinal samples collected in 2018. PrC31 shared 90.7% and 92.0% nucleotide identities to the genomes of SARS-CoV-2 and the bat SARSr-CoV ZC45, respectively. Sequence alignment of PrC31 showed that several genomic regions, especially orf1a and orf8 had the highest homology with those corresponding genomic regions of SARS-CoV-2 than any other related viruses. Phylogenetic analysis indicated that PrC31 shared a common ancestor with SARS-CoV-2 in evolutionary history. The differences between the PrC31 and SARS-CoV-2 genomes were mainly manifested in the spike genes. The amino acid homology between the receptor binding domains of PrC31 and SARS-CoV-2 was only 64.2%. Importantly, recombination analysis revealed that PrC31 underwent multiple complex recombination events (including three recombination breakpoints) involving the SARS-CoV and SARS-CoV-2 sub-lineages, indicating that PrC31 evolved from yet-to-be-identified intermediate recombination strains. Combined with previous studies, it is revealed that the beta-CoVs may possess a more complex recombination mechanism than we thought.